2016
DOI: 10.1037/dev0000091
|View full text |Cite
|
Sign up to set email alerts
|

Development of the updating executive function: From 7-year-olds to young adults.

Abstract: Updating information in working memory (WM) is a critical executive function responsible both for continuously replacing outdated information with new relevant data and to suppress or inhibit content that is no longer relevant according to task demands. The goal of the present research is twofold: First, we aimed to study updating development in 548 participants of 4 different age ranges--7-, 11-, and 15-year-olds and young adults--using the updating task devised by R. De Beni and P. Palladino (2004), which al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
47
0
6

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(58 citation statements)
references
References 71 publications
(137 reference statements)
5
47
0
6
Order By: Relevance
“…However, it is interesting that despite the evidence for enormous brain plasticity in children and a plethora of research demonstrating the effects of early environmental experiences on brain development, specifically within the context of parental caregiving and EF abilities, there is still little knowledge about associations between parenting behavior and EF skills in school-aged children between the ages 9 and 14. The PFC has an extended period of development (De Bellis, 2001; Gunnar et al, 2006) and due to the PFC's correlation with the development of EF skills, there are substantial changes in EF functioning across and beyond childhood (for reviews see Diamond, 2006; Garon et al, 2008), with some aspects of EF skills developing far beyond adolescence (Carriedo et al, 2016). It has also been previously demonstrated that parent-child relationships and their correlations with EF in children are culturally sensitive (Portes et al, 2000), however, to the best of our knowledge, there has been no study investigating the associations between parenting behaviors and school-age children's EF skills within a European context.…”
Section: Introductionmentioning
confidence: 99%
“…However, it is interesting that despite the evidence for enormous brain plasticity in children and a plethora of research demonstrating the effects of early environmental experiences on brain development, specifically within the context of parental caregiving and EF abilities, there is still little knowledge about associations between parenting behavior and EF skills in school-aged children between the ages 9 and 14. The PFC has an extended period of development (De Bellis, 2001; Gunnar et al, 2006) and due to the PFC's correlation with the development of EF skills, there are substantial changes in EF functioning across and beyond childhood (for reviews see Diamond, 2006; Garon et al, 2008), with some aspects of EF skills developing far beyond adolescence (Carriedo et al, 2016). It has also been previously demonstrated that parent-child relationships and their correlations with EF in children are culturally sensitive (Portes et al, 2000), however, to the best of our knowledge, there has been no study investigating the associations between parenting behaviors and school-age children's EF skills within a European context.…”
Section: Introductionmentioning
confidence: 99%
“…There were no significant differences in fluid intelligence between participant assigned to order 1 and those assigned to order 2 ( t = −1.28; p > .20). We selected this group of participants because of two main reasons: (1) In Experiment 1, we have shown that the performance on the bat/ball item of 15‐year‐olds participants was similar to the performance of adults, and (2) developmental studies have shown that most executive functions have been developed by approximately the age of 15 (see Carriedo, Corral, Montoro, Herrero, & Rucián, ; Huizinga et al ., )…”
Section: Methodsmentioning
confidence: 99%
“…There were no significant differences in fluid intelligence between participant assigned to order 1 and those assigned to order 2 (t = À1.28; p > .20). We selected this group of participants because of two main reasons: (1) In Experiment 1, we have shown that the performance on the bat/ball item of 15-year-olds participants was similar to the performance of adults, and (2) developmental studies have shown that most executive functions have been developed by approximately the age of 15 (see Carriedo, Corral, Montoro, Herrero, & Ruci an, 2016;Huizinga et al, 2006) 4 Materials and procedure The participants were evaluated regarding general intelligence, mathematical reasoning, reading comprehension, and various tasks that are most commonly used to investigate executive functions (Miyake et al, 2000): (1) updating or the ability to supervise, encode, and select the information that is relevant to the task at hand, replacing old information that is no longer relevant with new information that is relevant; (2) inhibition or the ability to inhibit dominant or preponderant information and automatic responses when they are not necessary to perform the task; and (3) shifting or cognitive flexibility, that is, the ability to change strategies, attention, or tasks when the subject has to perform multiple tasks, operations, or mental processes.…”
Section: Participantsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, monitoring involves the ability to focus attention and inhibit the desire to respond to distracting stimuli. Cognitive progress in monitoring skills starts at age three and eight, and is related to memory (when and how an event happened), allowing students to monitor how they makedecisions based on this pre-existing memory 31 . This skill was highlighted by teachers, as while performing academic tasks students must monitor their behavior, access information in their memory and make decisions while performing an activity.…”
Section: Discussionmentioning
confidence: 99%